Rejection Rate Analysis on Rail Wheels - N, Gayathri; E, Prakash; P, Manikandan; N, Karthick; S, Aravindh; M, Rohini (International Journal of Engineering and Technology, 2018)
These analysis ambitions to ascertain the major core cause of failures of rail wheels and to prevent the occurrence of same in future. One working model of train is developed to estimate the heat generated at brake pad-wheel and rail-wheel interfaces for locomotive and wagon wheels using the performance characteristics of brake blocks, the slip characteristics of wheel-rail traction and the resistance characteristics of a running train for given operating and braking conditions. The heat dissipation characteristics of rail-wheel and brake pad units interfaces in locomotive and wagon wheels and wheel running temperatures for different wheel profiles for different train running conditions are estimated. This work is carried out to identify the under-lying machinery of locomotive wheel failure due to widening and condemning of gauge. It has also accomplished the investigation on the impact of the type of brake block, wheel profile and braking conditions on locomotive wheel fiasco from gauge widening and condemning are also been carried out. It is suggested to use a high friction coefficient composite brake block results in higher wheel temperatures and cause large gauge changes, particularly for independent braking. Further, S-shaped wheels are found to be best suitable for avoiding undue gauge reduction or increase.Â